PROSPEK PENGATURAN UNRULY PASSENGER DI INDONESIABERDASARKAN PROTOKOL MONTREAL 2014 - Gledys Deyana Wahyudin, - (2019)
Unruly Passenger can threaten aviation security and safety, and cause delays or emergency landings. But due to loopholes on the existing laws, and lack of choice jurisdiction, unruly passenger are often unpunished. In public international law, the concept of jurisdiction has a strong relationship with the notion of sovereignty. Jurisdiction is a very important component in statehood and an authority for the state to make its legal decisions and judgments. The Montreal Protocol 2014 is an international legal instrument that is present to fill the legal loopholes in previously applicable regulations. The Montreal Protocol 2014 brought changes including the extension of jurisdiction, expanding the definition of violations committed in aircraft, right of recourse, and the role of In Flight Security Officer (IFSO). This thesis discusses Indonesia's interest to extend it's jurisdiction as regulated in the Montreal Protocol 2014, especially on the international flights. The increasing number of unruly passenger and the pressure from Indonesian airline companies to immediately ratify the Montreal Protocol 2014, the ratification of the Montreal Protocol 2014 in Indonesia is very important.